Development of iron-based catalyst for the production of hydrogen by thermocatalytic decomposition of methane - Tee, Huey Yi. (2012)
Iron-based catalysts were synthesized using the precipitation/ co-precipitation method for the thermocatalytic decomposition of methane to hydrogen. The metal source, precipitator, solvent and surfactant were varied to study their effects on the structural and catalytic performance of the catalysts. TEM, SEM and XRD were used to characterize the catalyst structures and by varying the catalyst synthesis conditions, iron-based oxides with various morphologies, such as diamond, rod and sphere-like structures, could be obtained.Introduction of methane during the initial reduction of the iron oxides played a critical role on yielding excellent catalytic results. TEM micrographs showed that two different carbon materials, carbon fibres and graphene layers were present during the catalytic decomposition process. The best catalytic activity was achieved by the catalyst which was prepared from iron nitrate, ammonia and water. Stepped-programmed temperature tests were employed in this study to assess the catalytic performance of the catalyst in the most efficient and effective way to obtain their optimized operating temperature and maximum conversion rate. Promising catalysts identified in the stepped-programmed temperature tests were again tested at fixed temperature to optimize their conversion rate and observe their stability.